2019
DOI: 10.3390/cancers11040572
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of Gap Junction Function and Cytokine Production in Response to Non-Genotoxic Polycyclic Aromatic Hydrocarbons in an In Vitro Lung Cell Model

Abstract: Polycyclic aromatic hydrocarbons (PAHs), prevalent contaminants in our environment, in many occupations, and in first and second-hand smoke, pose significant adverse health effects. Most research focused on the genotoxic high molecular weight PAHs (e.g., benzo[a]pyrene), however, the nongenotoxic low molecular weight (LMW) PAHs are emerging as potential co-carcinogens and tumor promoters known to dysregulate gap junctional intercellular communication (GJIC), activate mitogen activated protein kinase pathways, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 75 publications
0
19
0
Order By: Relevance
“…Studies have shown that connexins play a key role in mediating inflammation. For example, inflammation by polycyclic aromatic hydrocarbons in lung and liver epithelial cells results in the inhibition of gap junction intercellular communication through production of arachidonic acid, chemokines, TNF, and Cox-2 activation [17][18][19][20]. In activated peritoneal macrophages, inhibition Cx43 function through either pharmacologic administration or gene knockout improved survival, indicated by a reduction in cytokines during sepsis [21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that connexins play a key role in mediating inflammation. For example, inflammation by polycyclic aromatic hydrocarbons in lung and liver epithelial cells results in the inhibition of gap junction intercellular communication through production of arachidonic acid, chemokines, TNF, and Cox-2 activation [17][18][19][20]. In activated peritoneal macrophages, inhibition Cx43 function through either pharmacologic administration or gene knockout improved survival, indicated by a reduction in cytokines during sepsis [21].…”
Section: Introductionmentioning
confidence: 99%
“…While it is well established that environmental DEPs have many toxic effects on cells and tissues of the cardio-pulmonary system [33,54], this study suggests that the stomach stem cells are also a target for DEPs. In an in vitro model of mGS cell exposure to DEPs, viability, migration, release of oxidative stress markers, and expression of some genes and proteins were systematically analyzed.…”
Section: Discussionmentioning
confidence: 58%
“…Little is known about the effects of DEPs on stem/progenitor cells. Exposure of stem/progenitor liver cells and lung cells to polycyclic aromatic hydrocarbons present in DEPs induce epigenetic toxicity characterized by a reduction in gap junctional intercellular communications and activation of MAPK activity and signaling pathways of both inflammation and carcinogenesis [ 31 , 32 , 33 , 34 ]. However, exposure of endothelial progenitor cells to DEPs impairs their number and migration and causes the formation of reactive oxygen species [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Probably, the example of lung cancers found in persons never having been exposed to tobacco smoke, either as a smoker or a downstream target. 41-43…”
Section: No One “Thing” Causes Human Cancersmentioning
confidence: 99%